Industrial perspectives for personalized microneedles - Baker-Sediako, Remmi Danae; Richter, Benjamin; Blaicher, Matthias; Thiel, Michael; Hermatschweiler, Martin (Beilstein Journal of Nanotechnology, 2023)
Microneedles and, subsequently, microneedle arrays are emerging miniaturized medical devices for painless transdermal drug delivery. New and improved additive manufacturing methods enable novel microneedle designs to be realized for preclinical and clinical trial assessments. However, current literature reviews suggest that industrial manufacturers and researchers have focused their efforts on one-size-fits-all designs for transdermal drug delivery, regardless of patient demographic and injection site. In this perspective article, we briefly review current microneedle designs, microfabrication methods, and industrialization strategies. We also provide an outlook where microneedles may become personalized according to a patient’s demographic in order to increase drug delivery efficiency and reduce healing times for patient-centric care.
Keywords: 3D printing; microfabrication; microneedles; personalized medicine; transdermal drug delivery; two-photon polymerization